1979
DOI: 10.1139/f79-195
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Phosphorus and Nitrogen Deficiency in Five Algae in Culture

Abstract: Five freshwater algae (Chlamydomonas reinhardi, Scenedesmus quadricauda, Anabaena variabilis, Pseudoanabaena catenata, and Cryptomonas erosa) were grown in batch culture without nutrient limitation and with various degrees of P and N limitation. They were analysed for several aspects of composition and some metabolic activities of potential use as indicators of nutrient deficiency to aid in establishing values indicative of the presence or absence of nutrient deficiency. Ratios of N/C, P/C, N/P, protein/C, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
2
5

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(162 citation statements)
references
References 0 publications
10
145
2
5
Order By: Relevance
“…The lack of upregulation under the P-reduced treatment is potentially a result of experimental conditions designed to upregulate P stress not being limiting enough. In the case of Microcystis, deeper P-limiting conditions may be required for widespread upregulation of genes involved in phosphate metabolism, including APase (Healey and Hendzel, 1979;Harke and Gobler, 2013). Previous studies have found that APase activity is independent of phosphate concentrations when they are above 0.2 mM in the environment (Nausch, 1998), much lower than those used in this study, and may in fact be linked to cellular N/C ratios in phytoplankton (Myklestad and Sakshaug, 1983;Neddermann and Nausch, 2004).…”
Section: Insights Into Physiological Responses Of Microcystis To Nutrmentioning
confidence: 59%
“…The lack of upregulation under the P-reduced treatment is potentially a result of experimental conditions designed to upregulate P stress not being limiting enough. In the case of Microcystis, deeper P-limiting conditions may be required for widespread upregulation of genes involved in phosphate metabolism, including APase (Healey and Hendzel, 1979;Harke and Gobler, 2013). Previous studies have found that APase activity is independent of phosphate concentrations when they are above 0.2 mM in the environment (Nausch, 1998), much lower than those used in this study, and may in fact be linked to cellular N/C ratios in phytoplankton (Myklestad and Sakshaug, 1983;Neddermann and Nausch, 2004).…”
Section: Insights Into Physiological Responses Of Microcystis To Nutrmentioning
confidence: 59%
“…Different macromolecular components are associated with different cell functions, with proteins linked to basic functions of biosynthesis and cell division, and lipids and polysaccharides serving mainly as intracellular reservoirs of carbon and energy (Geider et al, 1986). These changes in carbon allocation provide important insights into metabolic strategies adopted by phytoplankton in response to differing environmental conditions; for example under poor growth conditions (low-phosphorus) phytoplankton may preferentially synthesize storage products such as polysaccharide and/or lipid rather than protein (Healey & Hendzel, 1979;Ganff et al, 1986;Kilham et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…L'activité phosphatase alcaline jouerait donc le rôle d'un indicateur de carence en phosphore minéral. De nombreux auteurs ont démontré que l'activité phosphatase alcaline était étroitement liée aux quantités de phosphore minéral disponibles dans le milieu et que de fortes concentrations en phosphore minéral répriment la synthèse de l'enzyme (Dilenfeldt & Gibson 1975, Healey & Hendzel 1979, Cembella et al 1984-85, Jansson et al 1988). …”
Section: Discussion Et Conclusionunclassified